THE ETHICAL FOUNDATIONS OF FAMILY IN AVICENNA'S PHILOSOPHY - Teshaev, Nutfullo Nasrulloevich (PT. Antis International Publisher, 2024)
In the following article, the multifaceted role of women in the upbringing of children is examined through the lens of Abu Ali Ibn Sina’s socio-philosophical views. The research delves into the dynamics of the relationship between men and women within the family unit, highlighting how these interactions influence the overall development of children. The study further explores the qualities that define an ideal and wise woman according to Ibn Sina, emphasizing her impact on the spiritual and moral upbringing of children. Additionally, the article discusses the personal expression of parents and how their behavior and values shape the character and ethics of their offspring. The duties and responsibilities of both parents in fostering a nurturing and morally sound environment for their children are scrutinized. This comprehensive analysis is supported by an extensive review of Ibn Sina’s works, alongside contemporary interpretations and sources that shed light on the enduring relevance of his ideas in modern contexts